E-Money and How It Can Influence the World Finance Market - WÓJCIK-CZERNIAWSKA Agnieszka (Communications of International Proceedings, 2022)
The economic dynamics that are increasingly fast in line with advances in information technology have important implications for the framework of monetary policy transmission mechanisms throughout the country. The existence of technology in the financial system especially the payment system not only has a positive impact on the acceleration of a country's economic growth and financial system development, but also presents its own challenges and the risks in changing the pattern of policy settings in the payment system. The rapid of information technology based on electronic finance (e-finance) has changed the financial system which is increasingly difficult to predict. The main purpose of this article is E-money and how it can influence the world finance market. In the study, the objective is to find out what factors influence the use of e-money in different areas in order to improve its use. In this research secondary research method is used. All data collected through other sources like, internet, books, magazines, libraries and finance market websites and other E-money platform. This research states the Expanded monetary unsteadiness could rise up out of the expanded flexibility of private cash creation, and from intermittent reaches a financial dead end into national bank cash that produce liquidity emergencies and uncertainty.
Keywords: Electronic Money; Financial Market; Monetary Policy; Economic dynamics